Neuroprotective and anti-inflammatory activity of Wyethia species: therapeutic potential for neurodegenerative diseases - Sagbo, Idowu Jonas; Soriano-Castell, David; Rebman, Jon; Maher, Pamela (Frontiers in Pharmacology, 2026)
Neurodegenerative diseases such as Alzheimer’s disease involve regulated forms of cell death, including oxytosis/ferroptosis, which are driven by oxidative stress and neuroinflammation. Targeting these regulated cell death pathways offers novel therapeutic opportunities. Wyethia is a small genus of flowering plants native to North America, traditionally used by Indigenous populations for medicinal purposes. Its ethnobotanical relevance and phytochemical diversity prompted investigation into its neuroprotective potential. This study examined eight Wyethia species for anti-inflammatory and neuroprotective activities. We evaluated protection against oxytosis/ferroptosis (induced by glutamate, erastin, and RSL3) in HT22 neuronal cells, energy loss using an ischemia assay in HT22 cells, and LPS-induced inflammation in BV2 microglial cells. W. ovata, W. helenioides, W. amplexicaulis and W. glabra exhibited strong neuroprotection (EC50 < 25 μg/mL), with W. ovata also demonstrating potent anti-inflammatory activity (EC50 = 15.2 μg/mL). Antioxidant assays (DPPH, lipid peroxidation) and measurement of total phenolic content (TPC) analysis revealed a correlation between high phenolic content and antioxidant activity, with W. ovata and W. amplexicaulis showing the highest TPC values (120–140 mg GAE/g). However, W. invenusta displayed strong neuroprotective effects despite low TPC, suggesting that other bioactive compounds such as terpenoids, or alkaloids may contribute to its activity. This highlights the complexity of phytochemical profiles and the potential presence of potent constituents beyond phenolics. These findings position Wyethia as a promising source of dual-action neuroprotective agents that target both oxytosis/ferroptosis and inflammation, warranting further phytochemical investigation.